Analysis of metallic medical devices after cremation: The importance in identification. Issue 2 (March 2017) - De Angelis, Danilo; Collini, Federica; Muccino, Enrico; Cappella, Annalisa; Sguazza, Emanuela; Mazzucchi, Alessandra; Cattaneo, Cristina
Abstract: The recovery of a charred cadaver raises many issues concerning personal identification; the presence of prosthetic materials may provide very important and decisive information. Who is involved in the recovery of a charred body or of burnt human fragments, should therefore be able to recognize medical devices even if modified by fire effects. Metallic residues (585 kg) that came from 2785 cremations were studied. Medical devices were then divided by type and material in order to esteem the representativeness of each typology. The study illustrates the great presence of metal medical devices that could be of great help in identifying bodies and underlines that metallic medical devices types and morphology should be known by forensic practitioner involved in identification cases and that this kind of material can still be identified by physician and dentists, even if exposed to very high temperatures. Highlights: Residues that came from 2700 cremations were studied. Great presence of metal medical devices was found among 585 kg of metal residues. Forensic practitioner should know metal medical devices morphology. This kind of material can still be identified even if burnt.